2020
DOI: 10.13004/kjnt.2020.16.e21
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Neuropathic Pain of Brachial Plexus Avulsion Mistaken for Amputation Stump Pain for 36 Years: A Case Report

Abstract: Following an amputation of the extremities, chronic neuropathic pain and discomfort, such as phantom limb pain (phantom pain), phantom sensation, and stump pain may occur. Clinical patterns of phantom pain, phantom sensation, and pump pain may overlap and these symptoms may also exist in one patient. Serious trauma to the upper limbs can result in brachial plexus avulsion (BPA). If BPA occurs at the same time as severe trauma of the upper extremity and the amputation of the upper limb is performed, chronic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Radiofrequency lesioning was used in 17 studies; Samii et al initially used cordotomy electrodes to perform the DREZ lesioning, but later reported switching to radiofrequency electrodes ( 12 ). Thermal coagulation using bipolar cautery was used in 8 studies ( 6 , 23 , 26 , 28 , 31 , 36 , 38 , 39 ). In one study, Sindou et al reported performing sharp incisions in the dorsolateral sulcus followed by dot coagulation using bipolar cautery ( 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiofrequency lesioning was used in 17 studies; Samii et al initially used cordotomy electrodes to perform the DREZ lesioning, but later reported switching to radiofrequency electrodes ( 12 ). Thermal coagulation using bipolar cautery was used in 8 studies ( 6 , 23 , 26 , 28 , 31 , 36 , 38 , 39 ). In one study, Sindou et al reported performing sharp incisions in the dorsolateral sulcus followed by dot coagulation using bipolar cautery ( 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven case series were based on the same patient population, and only the most recent case series published were included in further analysis (8)(9)(10)(11)(12). The final study list included 31 papers, all of which were case series (6, 7, 10, 12-36) and case reports (37)(38)(39). No randomized controlled trials were identified.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Brachial plexus avulsion causes characteristic pain and paralysis in the upper extremities but often goes undiagnosed for years due to trauma to the shoulder and arm 5,9,10) . Despite pain surgery for neuropathic pain in brachial plexus avulsion 5,9,10) , no surgical restoration of the function of the elbow and shoulder was possible because it was referred to the authors one year after a shoulder injury. Finally, the authors had an opportunity to identify and treat brachial plexus avulsion in a patient who presented with pain and paralysis in the left arm within 1 year of the injury.…”
mentioning
confidence: 99%